2018
DOI: 10.1002/jmri.26172
|View full text |Cite
|
Sign up to set email alerts
|

Esophageal carcinoma: Intravoxel incoherent motion diffusion‐weighted MRI parameters and histopathological correlations

Abstract: 1 Technical Efficacy: Stage 2 J. Magn. Reson. Imaging 2018.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
15
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 35 publications
7
15
2
Order By: Relevance
“…The finding of ADC and D in this study is in concordance with the previous study in differentiating the intermediate from malignant solid soft‐tissue tumors . An esophageal study demonstrated that D had a significantly higher performance than ADC in grading of malignant tumors . In addition, Ki‐67, as a reflection of the tumor cell proliferation, was moderately negatively correlated with D of OETs.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The finding of ADC and D in this study is in concordance with the previous study in differentiating the intermediate from malignant solid soft‐tissue tumors . An esophageal study demonstrated that D had a significantly higher performance than ADC in grading of malignant tumors . In addition, Ki‐67, as a reflection of the tumor cell proliferation, was moderately negatively correlated with D of OETs.…”
Section: Discussionsupporting
confidence: 91%
“…However, D* was not a significant parameter for the discrimination of borderline from malignant OETs. Our findings were similar to other studies in the differential diagnosis of solid soft‐tissue tumors, and grading of esophageal carcinoma . The high uncertainty and lower diagnostic performance of D* might be because of the low signal‐to‐noise ratio and the varying vascularity among different histological types of tumors.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…At present, the IVIM-DWI has been used to evaluate the pathological or blood perfusion status in the brain (5,6) and abdominal organs (7)(8)(9)(10)(11). However, few studies (12)(13)(14) have been performed regarding the diagnosis and pathological grade of esophageal carcinoma with MRI, because conventional MRI is limited in its ability to resolve the early esophageal cancer. As the constant progress achieved in this field, IVIM-DWI demonstrated the potential value for the diagnosis and pathological grade of esophageal carcinoma (12,14,15).…”
Section: Introductionmentioning
confidence: 99%
“…For example, diffusion weighted imaging (DWI) is a noninvasive approach to probe the molecular diffusion of water on the microscopic scale without contrast administration, and the apparent diffusion coefficient (ADC) value has been utilized to evaluate the treatment response to CRT in many cancers including esophageal carcinoma [8]. Nevertheless, only a few studies have evaluated the clinical significance of the capacity of DWI to predict the treatment response in patients with EC [911], and there is uncertainty about how to select the timing of observation post-therapy to avoid false negatives, and how to minimize the confounding factors that may interfere with the measurements [12].…”
Section: Introductionmentioning
confidence: 99%